2022
DOI: 10.1097/qai.0000000000002827
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Release Assay and Tuberculin Skin Test Performance in Pregnant Women Living With and Without HIV

Abstract: Background: HIV and pregnancy may affect latent TB infection (LTBI) diagnostics. Tuberculin skin test (TST) and newer generation QuantiFERON-TB Gold Plus (QFT-Plus) evaluations in pregnant women living with HIV (WLHIV) and without HIV are lacking. Methods:In this cross-sectional study, pregnant women underwent TST and QFT-Plus testing during antenatal care in Kenya. We estimated LTBI prevalence and TST and QFT-Plus performances. Diagnostic agreement was assessed with kappa statistic, participant characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
0
18
1
1
Order By: Relevance
“…We found that the QFT-Plus test positivity in this population of PLHIV was 39.7%, a rate corresponding to estimates from the general population in an equivalent context 33. This differs slightly from a similar study conducted among pregnant women in Kenya, where 35.8% of the pregnant women living with HIV had TB infection by QFT-Plus test positivity rate equivalent to those without HIV 32. In Nigeria, in a similar high HIV/TB burden setup, Aladesanmi et al found that 53% of PLHIV had TB infection 34.…”
Section: Discussioncontrasting
confidence: 83%
“…We found that the QFT-Plus test positivity in this population of PLHIV was 39.7%, a rate corresponding to estimates from the general population in an equivalent context 33. This differs slightly from a similar study conducted among pregnant women in Kenya, where 35.8% of the pregnant women living with HIV had TB infection by QFT-Plus test positivity rate equivalent to those without HIV 32. In Nigeria, in a similar high HIV/TB burden setup, Aladesanmi et al found that 53% of PLHIV had TB infection 34.…”
Section: Discussioncontrasting
confidence: 83%
“…Children in HIV/TB endemic areas are at high risk of Mtb infection, which can quickly progress to TB disease due to their developing immunity. 4,8,14,15 A systematic review and meta-analysis estimated a 20% TB risk for young children within 2 years of exposure, with the majority of children under 5 years developing TB disease within a few months of exposure. 2 Our findings are consistent with those of a randomized clinical trial conducted in western Kenya, assessing the efficacy of isoniazid in HIV-exposed infants to prevent primary Mtb infection, in which the majority of TST conversions occurring in the first year of life (8.6/100 PY), though cumulative Mtb infection incidence was lower in this cohort study (3.6/100 PY), which enrolled both HIV-exposed and unexposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Description of parent cohort design, and baseline maternal characteristics and results of baseline maternal QFT-Plus and TST testing in pregnancy have been previously reported. 14…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most existing studies use data from before the adoption of Option Bþ, which involves lifelong combination ART, often starting prepregnancy. We used a recent longitudinal study [24,25] to compare the growth and development of HEU and HUU children and to identify predictors of growth and development in the setting of universal material ART.…”
Section: Introductionmentioning
confidence: 99%